Draft Genome Sequence of a New Fusarium Isolate Belonging to Fusarium tricinctum Species Complex Collected From Hazelnut in Central Italy - Turco, Silvia; Grottoli, Alessandro; Drais, Mounira Inas; De Spirito, Carlo; Faino, Luigi; Reverberi, Massimo; Cristofori, Valerio; Mazzaglia, Angelo (Frontiers in Plant Science, 2021)
In summer 2019, during a survey on the health status of a hazelnut orchard located in the Tuscia area (province of Viterbo, Latium, Italy), nuts showing symptoms such as brown-greyish spots at the bottom of the nuts progressing upwards to the apex, necrotic patches on the bracts, and sometime on the petioles, were found and collected for further studies. This syndrome is associated to the Nut Gray Necrosis (NGN), whose main causal agent is Fusarium lateritium. Aiming to increase knowledge about this fungal pathogen, the whole genome sequencing of a strain isolated from symptomatic hazelnut was performed using long Nanopore reads technology in combination with the higher precision of the Illumina reads, generating an high quality genome assembly. The following phylogenetic and comparative genomics analysis suggested that this isolate is referable to Fusarium tricinctum species complex rather than Fusarium lateritium one, as initially hypothesized. Thus, the study demonstrated that different Fusarium species can infect Corylus avellana producing the same symptomatology. Also, it shed light onto the genetic features of the pathogen in subject, clarifying facets about its biology, epidemiology, infection mechanisms and host spectrum, with the future objective to develop specific and efficient control strategies.